Under-promising and over-delivering: pleasing the customer or strategic blunder?. Issue 7 (24th October 2017) - Topaloglu, Omer; Fleming, David E.
Abstract : Purpose: The paper aims to provide a theoretical and empirical examination of the relationship between service expectation management, expectation inducing agent and customer satisfaction. Design/methodology/approach: Based on the disconfirmation paradigm in services and the promise-keeping premise in psychology, the hypotheses are developed and empirically tested using three experiments that manipulated expectations, expectation inducing agent and service outcome. Findings: The findings provide reconciliation to the previous studies in services and show that effectiveness of expectation management strategy depends on the individual expectation thresholds and the expectation inducing agent. If customers patronize a firm expecting more, then over-delivering on the service promise results in a significant benefit. However, for those customers whose mental expectation threshold is exceeded, keeping promises is as effective as exceeding promises. Practical implications: The practical implication of this paper is that services managers should be cognizant of the mental expectation threshold of customers and be wise in utilizing the under-promise, over-deliver strategy. Originality/value: Using a threshold approach, this paper introduces a new perspective to service practitioners who are trying to manage expectations in a highly variable business environment. It also benefits service researchers who are trying to enhance the understanding of service expectation management.